PEOPLE OF THE OLDER AGE GROUP AS A SPECIAL SOCIODEMOGRAPHIC GROUP. HEALTH OF OLDER AGE COHORTS - Gorbaneva, Elena (Revista Inclusiones, 2021)
The population aging processes cause a reduction in the share of the employable population, which negatively influences the social infrastructure, financial support of pension systems, etc. All of the above forces the state to look for a way out of this situation. At the same time, the issue of raising the retirement age is painful for the population of any country, because it implies a change in the previously adopted social contract between the state and its citizens regarding the time of the beginning of the "well-deserved rest". Indeed, the creation of pension systems and the establishment of the retirement age for the old age pension mean the emergence of a legal boundary for old age, marking the moment when an individual turns from a payer of pension contributions to a recipient of pension payments.